The new federalism: Distributional conflict, voluntarism, and segregation - Ignatius J. Horstmann; Kimberley A. Scharf (The University of Western Ontario, Department of Economics, 2000)
Along with the rise in income inequality in the U.S., we have observed a simultaneous move toward fiscal devolution and increased government reliance on private provision of public goods. This paper argues that these phenomena are related. We describe a model of jurisdiction and policy formation in which the structure of government provision is endogenous and public good provision levels are determined by a political process that can exploit private motives for voluntary giving. The model predicts that an increase in income inequality leads to decentralization, with local jurisdictions becoming more income-homogeneous than the population as a whole. This reduction in local income heterogeneity, combined with a reduced tax base, results in increased reliance by government on private provision.
Keywords: H2; H7; 330; fiscal federalism; private provision of public goods; jurisdiction formation